Appropriate Contract Durations in the German Markets for On-line Reserve Capacity - Sebastian Just (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2010)
This paper explores the economic implications of different contract durations in markets for on-line (primary and secondary) reserve capacity in Germany with the crucial feature of separate markets for spot energy and reserve capacity provision. The analysis is based on an equilibrium model developed by Just and Weber (2008) for reserve markets. It reveals the implicit trade-off for the bidders and interdependencies between the reserve and the spot markets. The results clearly show that shorter periods (with resulting lower variations in overall electricity demand) lead to more efficient dispatch and market results. Not only prices in the reserve capacity markets are expected to be lower, but also spot market prices. As these benefits can be partially reaped by owners of large generation portfolios also under longer contract durations, it discriminates smaller generation companies and can potentially deter market participation. Further, the paper discusses security concerns against shorter contract durations. It is shown that the opportunity costs character of the reserve market implies sufficient incentives for supplying online reserve capacity. The concerns do not appear to be predominant and it should be possible to manage them appropriately.
Keywords: L94; L11; D41; D44; 330; electricity markets; contract duration; power systems reserve; ancillary service; primary reserve; secondary reserve; spinning reserve; opportunity costs; equilibrium model